Assessment of the Distribution of Antibiotics without a Prescription at Community Pharmacies in Zawia, Libya - Beshna, Ebtesam; Malod, Jalal; Benyusef, Najat (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: Antibiotic resistance (ABR) poses a risk to public health on a worldwide scale, increasing hospital stays, medical expenses, and mortality. Increased improper use of antibiotics fuels ABR. Objective: To determine the extent of antibiotic dispensing without prescription in Zawia and its environs (Libya). Methods: the cross-section was conducted between September and October 2023. A total of 100 dispensers participated by using a questionnaire with 100 samples, all the participants were from Zawia and environs. The questionnaire consisted of five parts. The first part included demographic data; the second part was indications for dispensing antibiotics without a prescription; the third part was antibiotics dispensed without a prescription; the fourth part, the dispenser ask questions and offer advice to patients; and the fifth part was the route of administration of antibiotics dispensing without a prescription. Results & Conclusion: despite the laws, we concluded that dispensing antibiotics without a prescription was nonetheless common in Zawia and environ. Although most community pharmacy professionals are aware that dispensing antibiotics without a prescription (DAWP) is prohibited and increases antibiotic resistance, they still frequently use it to treat common cold and diarrheal illnesses. Key words: Dispenser, Antibiotics, Non-Prescription.